Quantitative detection of Streptococcus mutans from saliva using FTATM elute cards and real-time polymerase chain reaction - Seghatoleslami, Sepideh; Ohlsson, Lars; Hamberg, Kristina; Carlsson, Peter; Ericson, Dan; Ljunggren, Lennart (Scientific Research Publishing, 2013)
Dental caries is a localized, transmissible, pathological infection process that ends up in the destruction of hard dental tissue. Numerous reports have shown the close relationship between salivary levels of Streptococcus mutans and dental caries. As S. mutans, is considered to be the principle etiological agent of dental caries, the development of a quick and convenient method for detection and quantification of these bacteria from patient saliva samples would simplify diagnosis and treatment. The purpose of this study was to compare a new means of quantifying bacteria using FTATM Elute cards and Real-Time Polymerase Chain Reaction to a conventional culture-based assay using oral S. mutans as a model sample. A total of 60 different saliva samples were investigated. The results show a significant negative correlation between the two methods, with a correlation coefficient of -0.577 (Spearman’s Correlation) and p < 0.01. The method demonstrates a high sensitivity, specificity and reliable quantitative results, covering a large range of bacterial concentrations.
Keywords: Streptococcus mutans; FTATM Elute Cards; Real-Time PCR